Earning quality in Islamic banks : International evidence - Hendra, Grandis Imama (Kulliyyah of Economics & Management Sciences, International Islamic University Malaysia, 2015)
The rapid growth of Islamic banks globally has shown a large awareness of Muslims. However, it may not be averted from potential risks that may reduce the popularity of Islamic banks, such as earnings management activities. The purpose of this study is to determine the extent of the quality of earning in Islamic banks. With distortions in earnings, Islamic banks are compromising the basic of the existence of profit sharing principle. By integrating the components of corporate governance, such as board independence, audit committee's expertise and SSB's expertise, this study aims to examine determinants of earning quality in Islamic banks. Banks characteristics are also examined to identify its significant influence on earning quality. 64 Islamic banks in 15 countries from MENA, ASIA and Europe are employed to be sample in this study. The main findings show that the earning quality of Islamic banks in ASIA is higher than in MENA. Moreover, the result documents that SSB's expertise, BIG 4 and leverage have a significant impact on earning quality in Islamic banks. None of corporate governance mechanisms has a significant influence on earnings quality, except SSB's expertise. This finding suggests on the improvement of sharia corporate governance mechanism to enhance the quality of earning. Studies on earning quality in Islamic banks are still limited. Major theoretical contributions includes that this study investigate earnings quality of Islamic banks worldwide. Understanding the role of corporate governance to curb earning management activities in Islamic banks makes this study unique.